Finding out about hydropowe - Matt Doedon; Doeden,Matt (Minneapolis: Lerner Publications Company, 2015)
Did you know people can turn the energy in rushing water into electricity? This hydropower can run the computer and the lights in your home
Keywords: JUVENILE NONFICTION General; Water-power